An alternative way of estimating anodic and cathodic transfer coefficients from PEMFC polarization curves - Danilov, Valery; Tade, Moses (Elsevier BV, 2010)
This study presents a new technique for estimating cathodic and anodic charge transfer coefficients from fuel cell voltage–current curves. In contrast to conventional approach, the new technique allows estimation of anodic and cathodic charge transfer coefficients simultaneously from integral characteristics of voltage–current curves. Case studies illustrate the parameter estimation from PEMFC polarization curves. The new technique is compatible with available parameter estimation methods.